Efektivitas Pelatihan Peer Counselor untuk Meningkatkan Pengetahuan dan Keterampilan Praktik Konseling Dasar Siswa - Fatmawiyati, Jati; Puspitasari, Dwi Nikmah; Hapsari, Ayu Dyah; An-Nisa, Lhulu; Artha, Sholicahtud Devytta; Andayani, Sri (Flourishing Journal, 2026)
The imbalance between school counsellors and students limits the effectiveness of psychosocial services, requiring preventive student-empowerment approaches. This study aimed to examine the effectiveness of peer counsellor training in improving students’ knowledge and basic counselling practice skills. A quasi-experimental one-group pretest-posttest design was conducted with 26 vocational high school students selected through purposive sampling. Instruments consisted of a basic counselling knowledge questionnaire and practice observation sheets, and data were analysed using a paired sample t-test. Results indicated a significant post-training improvement (p < .001; d = 1.135), with mean scores increasing from 119.6 to 151.9. The findings suggest that integrating counselling concepts, ethics, empathic communication, role-play simulation, and structured feedback facilitates the transformation of declarative knowledge into procedural competence and enhances self-efficacy. The training also strengthened interpersonal readiness to provide peer support as an extension of school counselling services. In conclusion, peer counsellor training effectively improves students’ basic counselling competencies and offers a collaborative strategy to expand access to school mental-health services, although further controlled and longitudinal studies are recommended to strengthen external validity. AbstrakKeterbatasan rasio guru bimbingan dan konseling dengan jumlah siswa menyebabkan layanan psikososial di sekolah belum optimal, sehingga diperlukan pendekatan preventif berbasis pemberdayaan siswa. Penelitian ini bertujuan menguji efektivitas pelatihan peer counselor dalam meningkatkan pengetahuan dan keterampilan praktik konseling dasar siswa. Metode penelitian menggunakan kuasi eksperimen dengan desain one-group pretest post-test pada 26 siswa sekolah menengah kejuruan yang dipilih secara purposive. Instrumen berupa kuesioner pengetahuan konseling dasar dan lembar observasi praktik, sedangkan analisis data menggunakan paired sample t-test. Hasil menunjukkan peningkatan signifikan skor pasca pelatihan (p < 0,001; d = 1,135) dengan kenaikan mean dari 119,6 menjadi 151,9. Pembahasan mengindikasikan bahwa kombinasi psikoedukasi konsep konseling, etika, empati, role-play, dan umpan balik reflektif memfasilitasi transformasi pengetahuan deklaratif menjadi keterampilan prosedural serta meningkatkan efikasi diri peserta. Pelatihan juga memperkuat kesiapan interpersonal dalam memberikan dukungan sebaya sebagai perpanjangan layanan konselor sekolah. Sehingga, pelatihan peer counselor efektif meningkatkan kompetensi konseling dasar siswa dan berpotensi menjadi strategi kolaboratif untuk memperluas akses layanan kesehatan mental di sekolah, meskipun penelitian lanjutan dengan kelompok kontrol dan follow-up diperlukan untuk memperkuat validitas eksternal.